Properties of medium density fiberboard from rubberwood and leucaena in relation to wood ratio and resin content / Nur Othman Suratman - Suratman, Nur Othman (Faculty of Applied Sciences, 2015)
Properties of Medium Density Fiberboard (MDF) from Rubberwood and Leucaena In Relation to Wood Ratio and Resin Content